Jesus manifesto : restoring the supremacy and sovereignty of Jesus Christ - Sweet, Leonard I. (Thomas Nelson, 2010)
Expanding on the authors' 2009 online manifesto, this insistent, impassioned essay condemns as pharisaic those preachers who forgo a Christ-centered theology in favor of a cute, singular slogan or mission. The authors urge churches to focus on the man who embodies the entire religion. To do so, readers must learn the subtle distinction between following Christ and realizing Christ already lives within them. --from publisher description